Knockdown of USP8 inhibits prostate cancer cell growth, proliferation, and metastasis and promotes docetaxel’s activity by suppressing the NF-kB signaling pathway - Islam, Md. Tariqul; Chen, Fang-Zhi; Chen, Han-Chun; Wahid, Abdul (Frontiers in Oncology, 2022)
Ubiquitin-specific protease 8 (USP8) is recently reported to involve in tumorigenesis. Prostate cancer (PCa) is the most diagnosed malignancy among men, but USP8's role in PCa is not yet investigated comprehensively. Therefore, the PCa cell lines DU145 and PC3 were transfected with USP8 siRNA or overexpressing vector together with or without docetaxel. The silencing USP8 and docetaxel treatment reduced cell viability, and migration, and promoted apoptosis. In contrast, USP8 knockdown was found to enhance docetaxel anti-tumour activity. In contrast, increased cell viability and migration were noticed upon USP8 overexpression, thereby decreasing apoptosis and suppressing docetaxel anti-tumor activity. Notably, although the EGFR, PI3K, and NF-kB were found to be increased in both USP8 overexpression and docetaxel treatment, it significantly attenuated the effects in USP8 silencing followed by with or without docetaxel. Although EGFR silencing decreased PI3K and NF-kB activation, overexpression of USP8 was shown to counteract SiEGFR's effects on NF-kB signalling by increasing PI3K expression. Our findings revealed that USP8 plays an oncogenic role in PCa and can suppress docetaxel activity. Additionally, as the EGFR/PI3K/NF-kB was previously reported to develop docetaxel resistance, the combination treatment of USP8 knockdown with docetaxel might be a potential PCa therapeutic.